PRAISE OF WISDOM AND CULTIVATION OF INTELLECT IN “SHAHNAMEH” BY HAKIM FIRDAWSI (Scientific journal of the Fergana State University, 2025)
This article discusses the praise of wisdom and the promotion of intellect in Hakim Abul-Qasim Ferdowsi’s “Shahnameh”. Ferdowsi of Tus is considered one of the most illustrious figures in the thousand-year history of Persian and Tajik literature. Through his immortal masterpiece, “Shahnameh”, he gained worldwide fame. The authors of the article seek to explore the themes of wisdom, knowledge, and enlightenment found in various tales of “Shahnameh” and to analyze them in depth.